Cu-loaded polyurethane to reduce ureteral stent microbes adherence and regulation of the inflammation response to RAW264.7 - Li, Hongwei; Zhao, Jing; Wang, Zhenyu; Hu, Jiyuan; Zhao, Jinlong; Awonusi, Bukola O.; Li, Jianzhong; Fan, Lianhui (Frontiers in Materials, 2023)
Introduction: Ureteral stents blocked with encrustation are a common clinical complication and affect bacteria colonization and inflammatory response. In this study, different concentrations of copper (0.25, 0.5, 1, 1.5, and 2 g/L) were immobilized on polyurethane (PU) that showed functionalization of microbe resistance and regulation of the inflammation response to RAW264.7. Methods: X-ray photoelectron spectroscopy (XPS), atomic force microscope (AFM) and static water contact angles were used to analyze the surface characterization. Proteus mirabilis resistance test and adhesion of cells by SEM were carried out to evaluate the antibacterial property of Cu-bearing samples. Cell cytotoxicity assay and apoptosis were used to obtain acceptable concentrations of PU-Cu. The morphology of cells was used to observe the occurrence of pseudopodia after contact with PU-Cu. Would healing assay and Transwell invasion assay were carried out to observe the migration and recovery of macrophages. IL-6 and IL-10 were used to evaluate the secretion of pro-/anti-inflammatory cytokines. Results: X-ray photoelectron spectroscopy (XPS), atomic force microscope (AFM), and static water contact angle measurement were used to confirm successful immobilization of Cu on PU. Plate counting assay and observation of adhered cells by SEM demonstrated that the antibacterial performance of PU-Cu against Proteus mirabilis increased with the amount of Cu loading in a dependent manner. Furthermore, the CCK-8 assay and apoptosis test suggested an acceptable cytotoxicity of PU-Cu at concentrations of 0.25, 0.5, and 1 g/L. The morphology of cells observed by SEM showed reduced occurrence of pseudopodia after contact with PU-Cu. Wound healing and transwell invasion assays manifested that migration and recovery of macrophages were improved by PU-Cu. ELISA of IL-6 and IL-10 demonstrated that PU-Cu could regulate inflammatory cytokines toward anti-inflammatory functionalization.